2017
DOI: 10.1080/2162402x.2017.1328337
|View full text |Cite
|
Sign up to set email alerts
|

IL-18 receptor marks functional CD8+ T cells in non-small cell lung cancer

Abstract: IL-18 is an inflammasome-related cytokine, member of the IL-1 family, produced by a wide range of cells in response to signals by several pathogen-or damage-associated molecular patterns. It can be highly represented in tumor patients, but its relevance in human cancer development is not clear. In this study, we provide evidence that IL-18 is principally expressed in tumor cells and, in concert with other conventional Th1 cell-driven cytokines, has a pivotal role in establishing a pro-inflammatory milieu in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
21
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 29 publications
(23 citation statements)
references
References 28 publications
2
21
0
Order By: Relevance
“…Results from mouse models demonstrate that the rescue of CD8 þ T-cell effector functions, such as Tbet-driven IFNg release, is key to success (17,41,42). In human cancer, we demonstrated that IFNg production can be recovered ex vivo selectively in Tbet hi tumor-infiltrating CD8 þ T cells (43). In line with previous findings in other mouse models (41), we found that Wnt3a neutralization exerted immunological effects mostly at the tumor site and not in the spleen, highlighting the relevance of tumor-infiltrating effector T-cell reactivation, rather than na€ ve or central memory T-cell expansion.…”
Section: Discussionmentioning
confidence: 80%
“…Results from mouse models demonstrate that the rescue of CD8 þ T-cell effector functions, such as Tbet-driven IFNg release, is key to success (17,41,42). In human cancer, we demonstrated that IFNg production can be recovered ex vivo selectively in Tbet hi tumor-infiltrating CD8 þ T cells (43). In line with previous findings in other mouse models (41), we found that Wnt3a neutralization exerted immunological effects mostly at the tumor site and not in the spleen, highlighting the relevance of tumor-infiltrating effector T-cell reactivation, rather than na€ ve or central memory T-cell expansion.…”
Section: Discussionmentioning
confidence: 80%
“…5D and F), suggesting additional factors might influence this heterogeneity. Expression of the transcription factor Eomes is associated with exhausted T cells (23)(24)(25)(26)(27)(28), and our intracellular flow cytometric assessment of Eomes revealed high expression in the CD8 þ TILs, with a significant negative correlation (r 2 ¼ 0.67, P < 0.0001) to IFNg production ( Fig. 6A).…”
Section: Eomes Expression In Cd103 þ T Rm Cells Is Associated With Lomentioning
confidence: 86%
“…In addition, it described for the first time the role of a single nucleotide polymorphism modulating CD39 expression on CD8 + TILs, and supported the possibility that CD39 expression may represent a valid biomarker of partially exhausted CD8 + TILs, and even a novel immune checkpoint for restoring T-cell exhaustion. 26,27 Given the importance of CD8 + TILs in solid cancers and their impact on cancer survival, 28 and because the current checkpoint inhibitors (eg, ant-PD-1, anti-CTLA-4, anti-PDL-1 monoclonal antibodies [mAbs]) are not efficient for all tumor types or cause partial remission in the majority of tumors, [29][30][31][32] innovative immunotherapy strategies, particularly based on the combination of different approaches including new inhibitors providing immune check point blockade (ICB), [33][34][35] can strongly impact the phenotypic and functional features of CD8 + T cells in the TME.…”
Section: Introductionmentioning
confidence: 99%